The effect of bispectral index monitoring on cognitive performance following sedation for outpatient colonoscopy: a randomized controlled trial - Sargin, Mehmet (2019)
BACKGROUND: Bispectral index (BIS) monitoring can positively affect cognitive performance through decreasing the use of sedative agents. We aimed to evaluate the effect of BIS monitoring on early cognitive performance among patients undergoing sedation for colonoscopy. DESIGN AND SETTING: Randomized, controlled trial in a university hospital. METHODS: 100 patients were randomized into two groups. In the monitored group (n = 50), the depth of anesthesia was monitored using the BIS, and BIS scores were maintained between 60 and 80. In the usual care group (n = 50), BIS monitoring was not performed. To determine the patients’ baseline cognitive per-formance levels, the mini-mental state examination (MMSE), Trieger dot test (TDT) and clock drawing test (CDT) were used. The patients’ post-procedure cognitive performance levels were determined when they were classified as ready for discharge. RESULTS: The total volume (mg) of propofol used [median (range) IQR] in the sedation procedure was lower in the monitored group [100 (50-200) 100-140] than in the usual care group [150 (75-200) 100-200] (P < 0.001). The discharge scores [mean (SD)] using MMSE and CDT were higher in the monitored group [26 (3) and 3 (1), respectively] than in the usual care group [23 (3) and 2 (1), respectively] (P = 0.002 and P = 0.002, respectively). The discharge scores using TDT [mean (SD)] were lower in the monitored group [11 (7)] than in the usual care group [15 (11)] (P = 0.033). CONCLUSION: BIS monitoring among sedated patients was associated with lower propofol use and smaller decline in cognitive performance. CLINICAL TRIAL REGISTRATION: This trial was registered in the Australian New Zealand Clinical Trial Reg-istry (ACTRN12617000134325).